A review on myocarditis with preserved ejection fraction: Diagnosis and treatment - Nasim Naderi; Sepideh Jafari Naeini; Zahra Hosseini (Research in Cardiovascular Medicine, 2021)
Myocarditis with preserved ejection fraction (MCpEF) is a subgroup of myocarditis with normal or near-normal left ventricular systolic function. Its prevalence has been reported to be low, and there are limited data about the diagnostic strategy, management, and outcome. Initial manifestation of myocarditis can be new-onset heart failure, acute coronary syndrome-like presentation, life-threatening arrhythmia, or even sudden cardiac death. Echocardiography with two-dimensional speckle-tracking mode and cardiac magnetic resonance imaging have pivotal roles in diagnosis and management of the disease. The present study is based on a research on “myocarditis preserved ejection fraction (EF)” or “ myocarditis with normal EF” mainly in PubMed, Google Scholar, and Embase databases. The search focused on the aspects of the disease which is not usually mentioned clearly. In contrast to the myocarditis as a general concept, the total number of clinical studies or case reports in the context of myocarditis with preserved EF is really low. Most treatment strategies have been based on the patient's initial presentation, and there are not enough clinical trials or long-term follow-up studies to confirm the most accurate diagnostic and therapeutic approach. In conclusion, although MCpEF has been known as a subgroup of myocarditis with specific clinical and imaging features, there are still a lot of questions about the diagnosis, management strategy, and patient prognosis which require further studies to be investigated.